PENDIDIKAN MORAL DALAM PERSPEKTIF PENDIDIKAN ISLAM - Mulya Hasanah (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon)
Moral Education in Islamic Education Perspective is a social phenomenon in society that is contrary to cultural traits or values, as well as religious values in the school community. This article aims to describe the values associated with norms in moral education in the community environment and how important moral education in the school community environment. Subjects in this study using a variety of literature consisting of books and research results of others who used and studied scientifically. This research uses qualitative approach with study literature technique. Based on the results of the analysis of study literature data obtained research results indicate that from various perspectives of moral education theory in accordance with the perspective of Islamic education is necessary, in order to establish norms of moral education in accordance with the characteristics or cultural values and religious values in society school environment through the view of Sufism.